Pragmatyczna racjonalność religii i religijności w ujęciu Williama Jamesa - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2010)
Zbigniew Drozdowicz – PRAGMATIC RATIONALITY OF RELIGION AND RELIGIOSITY IN THE VIEWS OF WILLIAM JAMES Nowadays the term “pragmatism” functions as a key-word applicable to many “clockworks”, so not using it may be regarded as an act of arrogance in solving difficult problems. A major contri-bution in the popularization of the term had William James. His works make out an attempt answering what was and is the goal of followers of pragmatism and as well an attempt to provide an answer to the criticism of pragmatism. In this article I recall general theory and views of prag-matism and the concept of religion and religiosity linked with it. From this view follows a as-sumption, that it may and should have a rational character, but only when they are approached pragmatically. The view of W. James in this matter I take as an important and keeping an actual virtue voice in the discussion on rationality in general, and religion and religiosity in particular.